Positive Discipline: Behavioral Management Skills for Parents and Teachers Part 1—Types of Misbehaviors and Keys to Success - Victor Harris; Whitney Fung; Sarah Ellis; Alison Schmeer (EDIS)
“Before I got married I had six theories about bringing up children; now I have six children, and no theories.” — John Wilmot